Active Learning using Quiziz in Procedure Text Class XI SMK Nusantara 02 Kesehatan - Maulinda, Rerin (International Journal of Language Pedagogy, 2021)
In this COVID-19 situation, it is a challenge for teachers to still be able to create fun, interesting and active learning. Although learning is carried out remotely or online, teachers must be able to increase student activity. Although learning is carried out remotely or online, teachers must be able to increase student activity. Student activity can be created through the application of interesting learning media. One of the interesting learning media in online learning is using the Quiziz educational game. This quiziz educational game usually uses a laptop or smartphone and can be carried out anywhere. The Quiziz educational learning is used for learning Procedure Text in class XI SMK Nusantara 02 Kesehatan. Through the descriptive method, this learning is supported by material observation, evaluation and interviews. The results obtained are that students enjoy this educational game and understand the material available in the Quiziz application faster.